THE INFLUENCE OF THE UZBEK LANGUAGE ON THE PRONUNCIATION OF ENGLISH - Umarova , Nigoraxon (QO‘QON UNIVERSITETI XABARNOMASI, 2026)
Pronunciation is an essential component of communicative competence in English as a Foreign Language (EFL), yet many learners experience persistent pronunciation difficulties despite years of formal instruction. One of the major causes of these difficulties is first language interference. This study investigates the influence of the Uzbek language on the pronunciation of English sounds by Uzbek-speaking EFL learners. The research examines both segmental features, including consonants and vowels, and suprasegmental features such as stress and intonation. Data were collected through pronunciation tests and audio recordings of learners’ spoken English. The findings indicate that the absence of certain English phonemes in the Uzbek phonological system and differences in rhythmic patterns significantly contribute to pronunciation errors. The study highlights the importance of teacher awareness of first language influence and supports the use of explicit pronunciation instruction to improve learners’ intelligibility. Pronunciation is a critical aspect of communicative competence in English, directly affecting learners’ ability to convey meaning accurately and interact effectively. For Uzbek-speaking learners, the influence of their first language manifests not only in the substitution of unfamiliar English sounds with native equivalents but also in the application of native rhythmic and intonation patterns. These patterns can cause unnatural stress placement, monotone speech, and difficulties in producing connected speech, which may hinder intelligibility in real-life communication. In addition to segmental errors, such as mispronunciation of consonants and vowels absent in Uzbek, suprasegmental features including sentence stress, rhythm, and intonation are also affected by first language interference. Uzbek learners may struggle with stress-timed patterns and vowel reduction in unstressed syllables, resulting in speech that sounds less fluent and natural. This highlights the importance of addressing both segmental and suprasegmental aspects of pronunciation in instruction. Explicit pronunciation teaching, combined with awareness of first language influence, is essential to help learners overcome these challenges. Techniques such as focused listening, guided articulation practice, interactive speaking exercises, and the use of digital tools for immediate feedback have proven effective in improving learners’ intelligibility. By integrating pronunciation instruction into communicative activities, teachers can enhance learners’ confidence, fluency, and overall oral communication skills. Understanding the specific challenges faced by Uzbek-speaking learners allows English teachers to design more targeted and effective pedagogical strategies. This approach not only supports the accurate production of English sounds but also contributes to the development of learners’ overall communicative competence, enabling them to participate successfully in diverse English-speaking contexts.